Morphological and molecular characterization of three Helicotylenchus species from Iran - Shokoohi, Ebrahim; Marais, Mariette; Fourie, Hendrika; Panahi, Hadi (Zootaxa, 2018)
Three Helicotylenchus species, namely Helicotylenchus digonicus, Helicotylenchus pseudorobustus and Helicotylenchus vulgaris were identified during a nematode survey conducted in Iran. The morphological and molecular characteristics of the species were defined. In addition, phylogenetic analysis of five Iranian Helicotylenchus populations based on 28S rDNA were done and showed the unresolved position of molecularly identified H. pseudorobustus and H. digonicus. However, populations of H. vulgaris and H. digonicus were placed close to each other. Phylogenetic analysis confirmed that molecularly characterized Helicotylenchus species formed a monophyletic clade. A detailed revision of the species is, however, needed. Illustrations and measurements for all species are provided.